Comparison of a novel real-time needle guidance ultrasound technique with conventional ultrasound for central venous line (internal jugular vein) access among patients in intensive care unit of UMMC / Chew Sou Chen - Chew , Sou Chen (2017)
Background Central venous line insertion is a common procedure performed in the intensive care unit and ultrasound guidance technique is widely practised currently. Despite the use of ultrasound, complications still persist. As exact needle location is often difficult to confirm with the conventional two dimension ultrasound. A novel real time needle guidance ultrasound approach allows the visualisation of the needle and tracks the needle during insertion. Objective To compare between the conventional ultrasound and novel real time needle guidance ultrasound technique for insertion of central venous line into the internal jugular vein. Methods This prospective, randomized controlled trial involved patients who underwent central venous line insertion in the intensive care unit of UMMC from Feb until Oct 2016. Participants were the doctors in anaesthesia who performed internal jugular vein cannulation via out of plane method using either the novel real time needle guidance ultrasound approach or conventional ultrasound. The primary outcome was to determine the performance time between the two techniques and the success rate. Participant" s satisfaction and complication rate were also evaluated. Results Since the performance time was not distributed normally, it is described as median (inter- quartile range, IQR). The median performance time for the novel real-time needle guidance and conventional ultrasound approach were 25.50(22) seconds and 15.00(17) seconds respectively. The p-value was 0.01 and therefore clinically significant. 100% of the operators were satisfied with the conventional method compared to only 88% for the novel real time needle guidance ultrasound method with a p- value of 0.012, which is clinically significant. Conclusions: Internal jugular vem cannulation using the conventional ultrasound guidance approach needed a shorter perfonnance time and had a higher satisfaction rate among the operators compared to the novel real-time needle guidance ultrasound approach.